The management of innovation in fruit production - Silva, A. L. [UNESP]; Santini, G. A. [UNESP]; Queiroz, T. R. [UNESP]; Lourenzani, W. L. [UNESP] (My University, 2011)
This research had as main hypothesis that the collective actions of cooperation between growers, through the Agricultural Association of Junqueirópolis induce the innovation process, by product and management innovation. Was used the method of field research. The type of research was descriptive and qualitative. Through the application of semi-structured survey questionnaires, it was possible to identify and understand as the process of learning and innovation in production activity. There was the occurrence of innovations with that aims improved the product quality and increased productivity. These innovations are induced from the external environment, being augmented in the shape properties through compulsory Agricultural Association of Junqueirópolis.
Keywords: Cooperation; Fruit culture; Management innovation; Networks; Process innovation; Product innovation